Importance of Special Stains As An Aid In Histopathological Diagnosis Of Oral Lesions – A Short Review - MAHAJAN, SAI SUDHA; SUKUMARAN, GHEENA; RAMANI, PRATIBHA; RAMASUBRAMANIAN, ABILASHA; R, HANNAH. (The journal of contemporary issues in business and government, 2021)
In histopathology, special stains help to enhance and assist with diagnosis. Special stains are usually performed after initial examination by H&E stained sections from a repeat cut-section on a paraffin block. Special staining technique provides valuable information in the evaluation of numerous abnormal or disease conditions. Therefore, this review focused to analyse the importance of special stains as an aid in diagnosis. Articles were searched in online databases, such as PUBMED, MEDLINE and Google scholar with keywords “oral lesions, special stains, histopathological diagnosis, importance.” Manual Search of Journals were also done. Articles were reviewed and analysed.The 3 relevant articles were reviewed which showed substantial importance of special stains in oral lesion biopsies. Special stains reveal the nature of keratin, collagen & elastic fibres, basal lamina in epithelium & tumor islands in oral Malignancies. Therefore, in modern pathology the role of special stains are helpful in detecting many oral lesions characteristic of pathologies, making it an important diagnostic tool.